Faktor yang Memengaruhi Keputusan Pembelian: Kualitas Produk, Kualitas Pelayanan, Kepercayaan dan Kepuasan Konsumen pada Produk Sneakers di Shopee Live Video Shopping - Ridha Alfia Zachra; Usep Suhud; Muhammad Fawaiq (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the factors that influence purchasing decisions with sneakers products on Shopee Live Video Shopping. The factors studied in this research are product quality, service quality, trust, and consumer satisfaction. This research was conducted in the Jakarta area. The population used is Shopee users in the Jakarta area. The method used in this research is quantitative, using primary data with a Likert scale as a measuring tool. Sampling in this study used a purposive sampling technique with 200 respondents (final sample). The data analysis technique in this research uses Structural Equation Model (SEM) using IBM SPSS 26 and AMOS 23 software. The results of this research show that product quality has a significant effect on consumer satisfaction and purchasing decisions. Service quality has a positive and significant effect on consumer satisfaction and purchasing decisions. Furthermore, trust has a positive and significant effect on consumer satisfaction and purchasing decisions. The results of this research also show that consumer satisfaction has a positive and significant effect on purchasing decisions.